Tanggung Jawab Showroom Atas Perbaikan Kendaraan Bermotor Bergaransi Perspektif Wahbah Zuhaili: Studi Kasus Kp. Pajak Pulo Jantan Kecamatan N.A IX -X Kabupaten Labuhanbatu Utara - Siti Mariah Sipahutar; Tetty Marlina Tarigan (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
Kp. Pajak Pulo Jantan or Pajak Pulo Village, District N.A IX -X North Labuhanbatu Regency there are cases where motor vehicle SHOWROOMs do not want to claim a damaged engine warranty from their customers even though in the previous sale and purchase agreement it has been agreed. The purpose of this study is to determine the completion of business actors' responsibility for repairing motor vehicles with a warranty perspective from Wahbah Zuhaili's perspective. How is the agreement for guaranteed motor vehicle repairs at the Kp. Pajak Pulo Jantan or District NA. Xi-X North Labuhanbatu. The research method used in this study is an qualitative method to make it easier to get data and also easier to analyze the problems in this study. The results showed that the warranty claim itself according to Wahbah Az-Zuhaili must be carried out because there has been an element of tadlis in the sale and purchase of the motorcycle unit. Not only that, the obligation to carry out this warranty claim is as evidence of fulfillment of the disgrace on an item. Then the obligation order of business actors is also in line with the Consumer Protection Law so that business actors can be prosecuted for committing unlawful acts.